Phospholipase C-δ1 and -δ3 Are Essential in the Trophoblast for Placental Development - Nakamura, Yoshikazu (American Society for Microbiology, 2005)
Phosphoinositide-specific phospholipase C (PLC) is a key enzyme in phosphoinositide turnover and is involved in a variety of physiological functions. We analyzed PLCδ1 knockout mice and found that PLCδ1 is required for the maintenance of skin homeostasis. However, there were no remarkable abnormalities except hair loss and runting in PLCδ1 knockout mice, even though PLCδ1 is broadly distributed. Here, we report that mice lacking both PLCδ1 and PLCδ3 died at embryonic day 11.5 (E11.5) to E13.5. PLCδ1/PLCδ3 double-knockout mice exhibited severe disruption of the normal labyrinth architecture in the placenta and decreased placental vascularization, as well as abnormal proliferation and apoptosis of trophoblasts in the labyrinth area. Furthermore, PLCδ1/PLCδ3 double-knockout embryos supplied with a normal placenta by the tetraploid aggregation method survived beyond E14.5, clearly indicating that the embryonic lethality is caused by a defect in trophoblasts. On the basis of these results, we conclude that PLCδ1 and PLCδ3 are essential in trophoblasts for placental development.